Pattern Detection Approach To Boolean Function Classification - Mustapha, Muhazam (2004)
This research is a study on Boolean functions classification by using pattern detector matrices corresponding to various classes of Boolean functions. Boolean functions are represented as a sequence of integers as a row vector, called Boolean block, which is a one to one mapping of 1-s and 0-s from the function's truth table. By this representation we study the binary pattern possessed by various classes of Boolean function.